2021
DOI: 10.3390/info12050208
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Awareness of Social Engineering in the Educational Sector in the Kingdom of Saudi Arabia

Abstract: Social engineering is one of the most inventive methods of gaining unauthorized access to information systems and obtaining sensitive information. This type of cybersecurity threat requires minimal technical knowledge because it relies on the organization’s human element. Social engineers use various techniques, such as phishing, to manipulate users into either granting them access to various systems or disclosing their private data and information. Social engineering attacks can cost organizations more than 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…A field cross-sectional survey (level of social engineering awareness) conducted in April 2022. Participants were selected from different Organizations, located at Riyadh City (KSA) [24]. The sample was divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A field cross-sectional survey (level of social engineering awareness) conducted in April 2022. Participants were selected from different Organizations, located at Riyadh City (KSA) [24]. The sample was divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it is critical to understand who these (human) hackers are [23]. Similarly, [24] stated that social engineering attacks include interpersonal interactions through face-to-face, telephone, or electronic communication with the recipient to manipulate them into divulging a company's confidential information. This argument aligns with [25].…”
Section: Hackers and Social Engineersmentioning
confidence: 99%
“…Only phishing method was discussed briefly. The age group were younger than 45, as they were 90% of participations [31].…”
Section: Appendixmentioning
confidence: 97%
“…Therefore, they require robust Internet security tools, to scan personal information, to prevent their system from any attacks. Alsulami, M.H., et al, (2021) have shown that there was a significant role for SE knowledge and mitigating the threats among students in the educational sector, and it has been conducted in [31]. Likewise, IIUM University in Malaysia was utilized a program to educate and enhance the awareness of students, however, significant number of students were replying to unverified anonymous emails.…”
Section: Approaches To Mitigate the Riskmentioning
confidence: 99%
“…Social engineering is one of the most creative methods to gain unauthorized access and obtain sensitive information from individuals or organizations (Alsulami, M.H., et al, 2021). SE is a collection of different techniques used to manipulate people into disclosing confidential information.…”
Section: Theoretical Background 21 Definition Of Social Engineeringmentioning
confidence: 99%